Penerapan Metode Eksperimen untuk Meningkatkan Aktivitas Pembelajaran dan Hasil Belajar Siswa pada Mata Pelajaran IPA Tentang Rangkaian Listrik di Kelas VI SD - Nurul Ismi; Rudi Ritonga (PT MITRA JURNAL INDONESIA, 2023)
Abstract Education plays a crucial role in developing individual potential. This research aims to enhance the learning outcomes of science for sixth-grade students at SD Bunayya Islamic School by implementing the experimental method. The research method used is Classroom Action Research (CAR) with four stages: planning, implementation, observation, and reflection. The results of the research show an improvement in student activity and learning outcomes from cycle I to cycle II. Student learning activities have significantly increased, such as the percentage of students paying attention to teacher explanations and successfully conducting experimental activities. Student learning outcomes have also improved, as evidenced by the increased percentage of students achieving mastery learning. From this research, it can be concluded that the use of the experimental method is effective in enhancing student activity and learning outcomes in science. The experimental method provides direct experiences to students, enhancing their understanding of science concepts. Therefore, the application of the experimental method is recommended in science education to improve student learning outcomes. Abstrak Pendidikan berperan penting dalam mengembangkan potensi individu. Penelitian ini bertujuan untuk meningkatkan hasil belajar IPA siswa kelas VI di SD Bunayya Islamic School dengan menerapkan metode eksperimen. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan empat tahapan: perencanaan, pelaksanaan, pengamatan, dan refleksi. Hasil penelitian menunjukkan peningkatan aktivitas dan hasil belajar siswa dari siklus I ke siklus II. Aktivitas belajar siswa mengalami peningkatan signifikan, seperti meningkatnya persentase siswa yang memperhatikan penjelasan guru dan mampu melaksanakan kegiatan eksperimen. Hasil belajar siswa juga meningkat, terbukti dari peningkatan persentase siswa yang mencapai ketuntasan belajar. Dari penelitian ini, dapat disimpulkan bahwa penggunaan metode eksperimen efektif dalam meningkatkan aktivitas dan hasil belajar siswa dalam IPA. Metode eksperimen memberikan pengalaman langsung kepada siswa, meningkatkan pemahaman mereka terhadap konsep-konsep IPA. Oleh karena itu, penerapan metode eksperimen dapat direkomendasikan dalam pembelajaran IPA untuk meningkatkan hasil belajar siswa.